Cenozoic aridization in Central Eurasia shaped diversification of toad-headed agamas (Phrynocephalus; Agamidae, Reptilia) - Solovyeva, Evgeniya N. (PeerJ, 2018)
We hypothesize the phylogenetic relationships of the agamid genus Phrynocephalus to assess how past environmental changes shaped the evolutionary and biogeographic history of these lizards and especially the impact of paleogeography and climatic factors. Phrynocephalus is one of the most diverse and taxonomically confusing lizard genera. As a key element of Palearctic deserts, it serves as a promising model for studies of historical biogeography and formation of arid habitats in Eurasia. We used 51 samples representing 33 of 40 recognized species of Phrynocephalus covering all major areas of the genus. Molecular data included four mtDNA (COI, ND2, ND4, Cytb; 2,703 bp) and four nuDNA protein-coding genes (RAG1, BDNF, AKAP9, NKTR; 4,188 bp). AU-tests were implemented to test for significant differences between mtDNA- and nuDNA-based topologies. A time-calibrated phylogeny was estimated using a Bayesian relaxed molecular clock with nine fossil calibrations. We reconstructed the ancestral area of origin, biogeographic scenarios, body size, and the evolution of habitat preference. Phylogenetic analyses of nuDNA genes recovered a well-resolved and supported topology. Analyses detected significant discordance with the less-supported mtDNA genealogy. The position of Phrynocephalus mystaceus conflicted greatly between the two datasets. MtDNA introgression due to ancient hybridization best explained this result. Monophyletic Phrynocephalus contained three main clades: (I) oviparous species from south-western and Middle Asia; (II) viviparous species of Qinghai–Tibetan Plateau (QTP); and (III) oviparous species of the Caspian Basin, Middle and Central Asia. Phrynocephalus originated in late Oligocene (26.9 Ma) and modern species diversified during the middle Miocene (14.8–13.5 Ma). The reconstruction of ancestral areas indicated that Phrynocephalus originated in Middle East–southern Middle Asia. Body size miniaturization likely occurred early in the history of Phrynocephalus. The common ancestor of Phrynocephalus probably preferred sandy substrates with the inclusion of clay or gravel. The time of Agaminae radiation and origin of Phrynocephalus in the late Oligocene significantly precedes the landbridge between Afro-Arabia and Eurasia in the Early Miocene. Diversification of Phrynocephalus coincides well with the mid-Miocene climatic transition when a rapid cooling of climate drove progressing aridification and the Paratethys salinity crisis. These factors likely triggered the spreading of desert habitats in Central Eurasia, which Phrynocephalus occupied. The origin of the viviparous Tibetan clade has been associated traditionally with uplifting of the QTP; however, further studies are needed to confirm this. Progressing late Miocene aridification, the decrease of the Paratethys Basin, orogenesis, and Plio–Pleistocene climate oscillations likely promoted further diversification within Phrynocephalus. We discuss Phrynocephalus taxonomy in scope of the new analyses.